Central banks and the rights and freedoms of the citizen - Schneider, Henrique (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
When central banks act, their policies and instruments impact not only on the economy, but on people’s rights as well. For this reason, central banks depend on politics, since politics is the organization of the polity – in which central banks and people’s rights are all incorporated. The same applies to an operational level: the central banks are interconnected with other institutions, for instance, the Executive Branch, economic agents and the whole economy through money, interest rates, and more recently, through “unorthodox monetary policy”. This paper examines how central banks operate pursuing the enlargement of the scope of their activities, the expansion of their means, and their reach. The aim of this article is to highlight that, by putting into practice what has been mentioned above, central banks reduce citizens’ freedom and rights. This analysis is applied to two cases, the “unorthodox monetary policy” and the ban on cash. Given these points, the possible remedies of the expansion of the activities of the central banks will be discussed.